Die Voorkoms van Insomnia en Rustelose Bene Sindroom by Bejaardes in 'n Tehuis in Bloemfontein - J.F. Venter; G. Joubert; M.J.V. van Vuuren (South African Family Practice)
Insomnia and Restless Legs Syndrome (one of the causes of insomnia) are under diagnosed and under treated by practitioners worldwide. Estimated prevalences of these conditions vary markedly. In addition, the lack of medication on the essential drug list to treat sleep disorders, incl udi ng RLS, necessitates studies to determine the prevalence of such disorders.